The impact of food price volatility on consumer welfare in Cameroon - Gilles Quentin Kane; Gwladys Laure Mabah Tene; Jean Joël Ambagna; Isabelle Piot-Lepetit; Fondo Sikod (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
The objective of this paper is to analyse the welfare effects of food price volatility on Cameroonian consumers. Using data from the third Cameroonian Household Consumption Surveys, the price elasticities are obtained from a Quadratic Almost Ideal Demand System model. Price elasticities are then used to evaluate the distributional impacts of food price changes in terms of compensating variation. The paper finds that: (a) poor households are the most affected by food price volatility and (b) the welfare losses from food price volatility depend on the extent of any price hike.
Keywords: D12; P46; Q18; 330; price volatility; consumer welfare; Cameroon